Study the best method of emergency response plan for chlorine gas facility at integrated shrimp pond area: article - Azman, Ainul Afifi; Abdul Rashid, Zulkifli (2017)
Chlorine is a type of chemical substance that possessed a hazardous and toxic characteristic. It may affect the human health as well as other living organisms in case were directly in contact with the substance. The effect on human health shall be concern as it will leads to the badly damages the respiratory system. Lung will experience the loss of most it tissues as the chlorine will enhance the degradation process if the sufficient amount of chlorine is inhaled (Sofia Jonasson, 2013). It will lead to the difficulties in breathing and for the worst may lead to fatal. It is therefore importance to prevent and for the best is to avoid the release of these toxic chemical from spreading into the atmosphere that will bring the unfortunate event towards the human races. Plant facilities that may containing the handling and storing a large amount of chlorine needs to be well design and also having an efficient of emergency response plan in case of the release of chlorine cannot be avoided. By having an emergency response plan will at least minimizing the risk of injuries and human exposed on chlorine. In this research, the passed accidental release of chlorine is studied to determine the impacts on environment and human upon released and also the root cause of the disaster also measured to avoid the same mistakes occur in the future. Besides, various emergency responses are studied based on their actions on tackling the emergency situation to be implied on the selected chlorine facility, shrimp pond owned by Isharp Sdn Bhd located in Terengganu.